2011
DOI: 10.1089/aid.2010.0204
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Transplacental Nucleoside Analogue Exposure and Mitochondrial Parameters in HIV-Uninfected Children

Abstract: Transplacental nucleoside analogue exposure can affect infant mitochondrial DNA (mtDNA). We evaluated mitochondria in peripheral blood mononuclear cells of children with and without clinical signs of mitochondrial dysfunction (MD) and antiretroviral (ARV) exposure. We previously identified 20 children with signs of MD (cases) among 1037 HIV-uninfected children born to HIV-infected women. We measured mtDNA copies/cell and oxidative phosphorylation (OXPHOS) NADH dehydrogenase (complex I) and cytochrome c oxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 14 publications
1
26
0
1
Order By: Relevance
“…1 Of particular concern are the clinical effects of nucleoside reverse-transcriptase inhibitors (NRTIs) on mitochondrial oxidative phosphorylation (OXPHOS) 2 and HIV protease inhibitors (PIs) on lipid and glucose metabolism. [3][4][5] Fatty acid oxidation (FAO) is an intramitochondrial metabolic pathway situated at the crux of mitochondrial OXPHOS, lipid catabolism, and glucose utilization.…”
Section: Introductionmentioning
confidence: 99%
“…1 Of particular concern are the clinical effects of nucleoside reverse-transcriptase inhibitors (NRTIs) on mitochondrial oxidative phosphorylation (OXPHOS) 2 and HIV protease inhibitors (PIs) on lipid and glucose metabolism. [3][4][5] Fatty acid oxidation (FAO) is an intramitochondrial metabolic pathway situated at the crux of mitochondrial OXPHOS, lipid catabolism, and glucose utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral neuropathy of nucleoside analogues is confirmed to associate with mitochondrial toxicity (Dalakas 2001;Youle 2007). It is easy for nucleoside analogues to penetrate blood-brain barrier and blood-testis barrier (Brogly et al 2011;Pavili et al 2010). In our previous study, we confirmed mtDNA lesions and oxidative damage in the cerebral cortex of AIDS patients with combined antiretroviral therapy (Zhang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PBMC mtDNA copies/cell was assayed by absolute quantitative real time PCR as previously published. 20 Each sample and standard were run in duplicate and the results were analyzed with Version 1.5.0 LightCycler 480 software.…”
Section: Laboratory Methodsmentioning
confidence: 99%